1979
DOI: 10.1073/pnas.76.6.2979
|View full text |Cite
|
Sign up to set email alerts
|

Mitrochondrial NADH dehydrogenase in cystic fibrosis.

Abstract: We have shown that skin fibroblasts from patients with cystic fibrosis (CF) and from carriers for CF [heterozygotes (HZ)] consume more 02 than do their controls. When the mitochondrial electron transport inhibitor rotenone was added to the cells, the relative inhibition of 02 consumption was CF > HZ > controls (P < 0.005 in both comparisons). Because rotenone specifically inhibits NADH dehydrogenase, [NADH:(acceptor) oxidoreductase, EC 1.6.99.31, which is the enzyme of energy-conserving site 1 of the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
1
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 21 publications
7
40
1
1
Order By: Relevance
“…Previous investigators have noted that mitochondria derived from CF fibroblasts consumed oxygen more rapidly than mitochondria derived from normal fibroblasts (25). This difference was associated with increased Ca++ uptake by CF fibroblast mitochondria (26) and an altered pH optimum of the mitochondria1 NADH dehydrogenase (25). We have not explored the relationship of these findings to our results.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous investigators have noted that mitochondria derived from CF fibroblasts consumed oxygen more rapidly than mitochondria derived from normal fibroblasts (25). This difference was associated with increased Ca++ uptake by CF fibroblast mitochondria (26) and an altered pH optimum of the mitochondria1 NADH dehydrogenase (25). We have not explored the relationship of these findings to our results.…”
Section: Discussioncontrasting
confidence: 46%
“…These data are consistent with the existence of a greater metabolic capacity in CF cells. Previous investigators have noted that mitochondria derived from CF fibroblasts consumed oxygen more rapidly than mitochondria derived from normal fibroblasts (25). This difference was associated with increased Ca++ uptake by CF fibroblast mitochondria (26) and an altered pH optimum of the mitochondria1 NADH dehydrogenase (25).…”
Section: Discussionmentioning
confidence: 81%
“…Possible explanatory mechanisms for low oxidative capacity and prolonged oxygen kinetics in subjects with CF are deconditioning, abnormalities at the mitochondrial level such as increased calcium concentration, 31 lower NADH dehydrogenase activity, 32 and higher pH optimum of NADH dehydrogenase. 33 Moreover, previous data 34 suggest a reduced efficiency of oxidative ATP synthesis in subjects with CF. In the literature, an association between the main CF gene mutation and raised energy expenditure in subjects with CF is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because this is an energy-dependent process, they studied fibroblast oxygen consumption and found that mitochondria from CF homozygotes consumed more O2 than controls, with heterozygous cells intermediate (23). The authors suggested that this organelle might be a suitable focus for further investigation and went on to demonstrate that the pH optimum for NADH dehydrogenase is different from enzymes derived from normal, CF, and CF heterozygote fibroblasts (53). Also, CF leucocytes accumulate more calcium than normal cells and calcium accumulation of normal cells can be increased to CF levels by exposure to CF serum (I), raising the question of an ionophore-like effect of CF serum, as had been suggested previously (10).…”
Section: Exocrine Glands and Their Productsmentioning
confidence: 99%